Inhibition of nuclear factor-κB activation improves non-nitric oxide-mediated cutaneous microvascular function in reproductive-aged healthy women - Content, Virginia G.; Williams, Auni C.; Alexander, Lacy M. (American journal of physiology. Heart and circulatory physiology, 2024)
The transcription factor nuclear factor-κB (NF-κB) regulates multiple aspects of innate and adaptive immunity by encoding for genes that participate in inflammation and impact endothelial function following NF-κB inhibition with salsalate treatment. Our results show that cutaneous microvascular function is increased through non-nitric oxide (NO)-dependent mechanisms following salsalate treatment in reproductive-aged healthy women. The transcriptional regulator nuclear factor-κB (NF-κB) is a mediator of endothelial dysfunction. Inhibiting NF-κB with salsalate is used to investigate inflammatory mechanisms contributing to accelerated cardiovascular disease risk. However, in the absence of disease, inhibition of NF-κB can impact redox mechanisms, resulting in paradoxically decreased endothelial function. This study aimed to measure microvascular endothelial function during inhibition of the transcriptional regulator NF-κB in reproductive-aged healthy women. In a randomized, single-blind, crossover, placebo-controlled design, nine healthy women were randomly assigned oral salsalate (1,500 mg, twice daily) or placebo treatments for 5 days. Subjects underwent graded perfusion with the endothelium-dependent agonist acetylcholine (ACh, 10 −10 to 10 −1 M, 33°C) alone and in combination with 15 mM N G -nitro-l-arginine methyl ester [l-NAME; nonselective nitric oxide (NO) synthase inhibitor] through intradermal microdialysis. Laser-Doppler flux was measured over each microdialysis site, and cutaneous vascular conductance (CVC) was calculated as flux divided by mean arterial pressure and normalized to site-specific maximum (CVC %max ; 28 mM sodium nitroprusside + 43°C). The l-NAME sensitive component was calculated as the difference between the areas under the dose-response curves. During the placebo and salsalate treatments, the l-NAME sites were reduced compared with the control sites (both P < 0.0001). Across treatments, there was a significant difference between the control and l-NAME sites, where both sites shifted upward following salsalate treatment (both P < 0.0001), whereas the l-NAME-sensitive component was not different ( P = 0.94). These data demonstrate that inhibition of the transcriptional regulator NF-κB improves cutaneous microvascular function in reproductive-aged healthy women through non-NO-dependent mechanisms. NEW & NOTEWORTHY The transcription factor nuclear factor-κB (NF-κB) regulates multiple aspects of innate and adaptive immunity by encoding for genes that participate in inflammation and impact endothelial function following NF-κB inhibition with salsalate treatment. Our results show that cutaneous microvascular function is increased through non-nitric oxide (NO)-dependent mechanisms following salsalate treatment in reproductive-aged healthy women.